Evaluation of Octhylphenol Effect on Development and Survival on Zebra Fish (Danio Rerio) During Different Ontogenic Period - Gabi Dumitrescu; Liliana Petculescu-Ciochina; Sorin Voia; Dorel Dronca; Liliana Boca (Scientific Papers Animal Science and Biotechnologies, 2023)
This paper is part of a complex study of our research collective that studies the toxic effect of the ethinylestradiolum, and some of the polyethoxylated alkylphenols on the growth and reproduction of the Zebra fish (Danio rerio) and of the common Carp (Cyprinus carpio). Our study aim was to evaluate the effect of octylphenol on growth and survival of zebra fish, from 21-115 days, and within 21-75 days of life. For this purpose, for each period under study, fishes were divided into three groups of 30 individuals, named: Lot 1 - Control, respectively lots 2 and 3, at which the administrated octylphenol concentrations were of 60 μg  L-1, respectively 100 μg  L-1. Fishes of the six groups were raised in 30-liters aquariums (30 fish / aquarium). The growth was measured by weighing and biometric measurements (total length, standard length, the length of the head, maximal height, minimal height and the mass of the body), while the surviving rate was established at the end of every period and at the end of the experiment, when we were able to calculate the total number of dead fish. Biometric study of the analysis performed in 75 days, 115 days respectively shows that octylphenol has negative influence on body development, and survival both, the highest percentage of mortality (46,66%) was registered at 100 μgL-1 concentration, between 21 -75 days.